Tree‐Ring Anatomy Improves the Reliability of Temperature Reconstructions Using Relict Wood - Stefan Klesse; Jesper Björklund; Marina V. Fonti; Daniel Nievergelt; Georg von Arx; Rashit M. Hantemirov; Vladimir V. Kukarskih; Lisbeth Garbrecht Thygesen; Nanna Bjerregaard Pedersen; Patrick Fonti (Geophysical Research Letters)
Abstract Tree rings are crucial for reconstructing past climates, with maximum latewood density (MXD) as a key metric. However, wood integrity is critical for accurate MXD‐based reconstructions, raising concerns when using potentially degraded relict wood. Quantitative wood anatomy (QWA) provides a morphometric alternative. We compared X‐ray and QWA‐derived density measurements from recent and five‐millennia‐old relict wood from Siberia's Yamal region. We measured bulk density and holo‐cellulose‐to‐wood ratio and employed spectroscopic analyses to identify chemical factors affecting density loss. The findings indicate likely abiotic degradation in relict wood, evidenced by significantly lower bulk density, holo‐cellulose content, and MXD than recent samples, while anatomical density and maximum radial cell wall thickness appeared unchanged. MXD‐based estimates suggested 1.7°C colder June‐August (JJA) temperatures 4,700 years ago, while QWA‐based estimates indicated 0.4°C warmer JJA temperatures than the 20th‐century mean. For relict wood with potential mass loss due to degradation, QWA is recommended over traditional MXD methods.